Simulasi Pengurangan Total Harmonic Distortion Pada Inverter Satu Fasa Dengan Metode Selective Harmonic Elimination - Liberty, Aprilia; Sukma, Dian Yayan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In Convertion process to be AC voltage and current, often happens some faults as harmonics. Harmonics effect in Electrical Power System is big enough causes overheated to equipment that has lower impedance. The propose of the research is to design and simulate an inverter to get minumum harmonics distortion values less than 5% as stated in Total Harmonics Distortion (THD). In this case, one phase fullbridge inverter performance uses Selective Harmonics Elimation (SHE) Method and Sinusoidal Pulse Width Modulation (SPWM) Method. SHE is used to eliminate ordinal harmonics carried by SPWM Inverter. SPWM only eliminates high ordinal harmonics therefore SHE is needed to eliminate lower ordinal harmonics. Determination of switching angle is solved by Newton Raphson Iteration Method. SPWM and SHE are analyzed based on simulation using MATLAB/SIMULINK 2016a software. SHEPWM inverter is equipped with LC filter to produce sinusoidal waveform output. The result of SHEPWM with LC filter design in single phase inverter produces 222 VAC ouput voltage and 0,28% of THD. Keywords : Inverter, Newton Raphson, SHE, SPWM, THD